Implementation of the Multi-Objective Optimization Method on the Basic of Ratio Analysis (MOORA) and Entropy Weighting in New Employee Recruitment - Karim, Abdul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The problems faced by the company in managing the selection of new employees must be done in the right way so that it can help a good work cycle. The employee recruitment process still uses manual methods so the Human Resource Development (HDR) division has to sort, select and select applicants one by one. The large number of applicants means that the Human Resource Development division often experiences difficulty in selecting prospective employees and there is subjectivity when deciding which employees fit the established criteria. To overcome the problem of making employee recruitment decisions, we will use the Multi-Objective Optimization method based on ratio analysis (MOORA) and weighting using Entropy. In research, data is collected based on the position of prospective employees. The results obtained in this research determine each position that will be accepted by 3 prospective employees, namely Sales Position, Position, Graphic Design, Accounting Staff, IT Support position, Sales Project.